Peta Mutu Pendidikan Madrasah Berdasarkan Akreditasi - Budi Susetyo; Cut N. Ummu Athiyah (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[QUALITY OF MADRASAH EDUCATION BASED ON ACCREDITATION]. The purpose of this article is to analyze a map of the quality of madrasah throughout Indonesia based on the results of accreditation in 2018 and 2019. The results of the analysis show that nationally the quality of madrasas has increased. However, the quality of madrasah varies greatly between provinces, levels, types of madrasah, and madrasah status. The accreditation results show that more than 80% of MI accredited at least B in 2018 and 2019, MTs in 2019 have reached 79.5%, while MA has only reached 73.3%. Provinces that have good quality at all levels of madrasah: DI Yogyakarta, West Java, and DKI Jakarta. In contrast, there are still 10 provinces that have a low quality, where madrasah accredited at least B is below 50%. Another result shows that the average fulfillment of the 8 quality standards for new madrasah is lower than that of re-accredited madrasah, the quality of private madrasah is lower than public madrasah. In general, the standards of education that are still low are the standards for teachers and education personnel and the standards for facilities and infrastructure.